Critical Boundaries of Activism in Public Relations in Pakistan: A Comparative Analysis of Effects of Professional Practices - Mudassir Mukhtar; Noshina Saleem; Stephen D. McDowell (JSSH, 2023)
This paper explores that how do professional and craft public relations practices affect department level of involvement to deal with the activist pressure in public and private sector organizations in Pakistan. The effects of role and model preferences in Pakistan are discussed in the light of assumptions of excellence theory of public relations. Models preferences are discussed within the parameters of four western models including press a gentry, public information, two-way asymmetrical and two-way symmetrical. Similarly, role preferences are elaborated within two major (manager and technician) and two minor roles (media relations and communication Liaison). The population of interest are highest ranking public relations practitioners heading public relations departments in public and private sectors organizations in Pakistan. Data is collected through a national survey using a random sample of 101 practitioners. Results support the major assumptions of the excellence theory. Although practitioners are using all four models as per their expertise to involve with the activist pressure but symmetrical communication proved comparatively most effective in dealing with activist pressure in public and private sector organizations in Pakistan.